A companion to modern art - Meecham, Pam (Wiley Blackwell companions to art history, 2018)
A Companion to Modern Art presents a series of original essays by international and interdisciplinary authors who offer a comprehensive overview of the origins and evolution of artistic works, movements, approaches, influences, and legacies of Modern Art.--Provided by publisher.